Metric study of the agrarian theme in the cuban´s newspaper Granma in the year 2019 - Peña-Borrego, Maida Daylin; González-Guitián, María Virginia; Rodríguez-Fernández, Rosa Margarita; de Zayas-Pérez, María Rosa (Revista General de Información y Documentación, 2021)
The behavior of the agrarian issue published in the Granma newspaper, in its daily printed edition during 2019, is analyzed to reveal the Cuban reality projected in this national dissemination medium of the Communist Party of Cuba (PCC). Bibliometric indicators are applied, such as: Monthly productivity, Productivity of topics by newspaper sections, Productivity by province,  Business entities and cooperative agricultural most representative; and well as the main agricultural research and technological innovation activities in this media. For the data analysis Excel and ToolInf softwares were used. A stable behavior was obtained in the approach to the subject in 60% of the annual issues, the second semester being the one with the highest number of publications in the Cuba section, the cover of the newspaper and in Letters to the Direction; giving broad coverage to issues related to monitoring and control of the agricultural sector, agricultural problems and agricultural production results, events, investments and infrastructure. The largest number of information was represented by the provinces: Pinar del Río, Cienfuegos and Granma; in which the main agricultural productions treated are corn, tobacco, rice and beans, and to a lesser extent the rest of the productions resulting from livestock, forestry, fishing and aquaculture activities. The most representative staters entities were the Ceballos Agroindustrial Company and Tabacuba, whose main purpose is to export its products. Scientific-technological activity directed to the cooperative sector
Keywords: Metric studies of information; agrarian production; Granma newspaper; Agriculture